Procalcitonin Level and Organ Dysfunction in Children with Sepsis: A Prospective Observational Study - Singh, Sandip Kumar; Sah, Vikash Kumar; Dekate, Parag Shankarrao (Journal of Nobel Medical College, 2022)
Background: Procalcitonin is produced in response to endotoxin or mediators released in response to bacterial infections and are reported to be sensitive predictor of sepsis and multiple organ failure. The main aim of this study was to correlate procalcitonin levels with the severity of organ dysfunction in children with sepsis. Materials and Methods: A prospective observational study was done among children aged >1 month - 18 years admitted for sepsis in level 4 pediatric intensive care unit at Rainbow children Hospital, Hyderabad from July 2018 to January 2020. Children with sepsis due to burns and trauma were excluded. Procalcitonin levels were assessed on days 1 and 5 and were analyzed using descriptive statistics. P value of < 0.05 was considered significant wherever applicable. Results: Among 369 cases, procalcitonin levels showed positive correlation with severity of illness and multiorgan failure as evidenced by pediatric risk of mortality III score (mean score 6.44 ± 3.79) and worst sepsis-related organ failure assessment score (mean score 7.11 ± 4.27) respectively. Duration of non-invasive ventilation, invasive ventilation, pediatric intensive care unit stay, and mortality were significantly high in children with higher procalcitonin level. Mean procalcitonin level were significantly higher in culture positive cases (65.79 ± 77.10) compared to culture negative cases (37.99 ± 45.81). Conclusion: In this study, positive correlation was observed between procalcitonin level and multiple organ dysfunctions in sepsis and septic shock.